Overcoming the morphological and efficiency limit in all-polymer solar cells by designing conjugated random copolymers containing a naphtho[1, 2-c:5, 6-c′]bis([1, 2, 5]thiadiazole)] moiety. Issue 46 (19th November 2018) - Xie, Ruihao; Li, Zhenye; Zhong, Wenkai; Ying, Lei; Hu, Qin; Liu, Feng; Li, Ning; Russell, Thomas P.; Huang, Fei; Cao, Yong
Abstract : We developed a series of ternary random copolymers for all-PSCs, which presented superior performances to their blended counterparts. Abstract : The ternary concept based on two electron donors and one electron acceptor has been deployed to extend the absorption as well as photovoltaic performance of all-polymer solar cells (all-PSCs). However, it is still challenging to achieve the delicate morphology of ternary blended bulk-heterojunction films through rational molecular design. To overcome these issues, herein, we designed and synthesized a series of narrow bandgap conjugated copolymers by combining two conjugated polymers with various molar ratios of the naphthobis[1, 2, 5]thiadiazole (NT) unit (namely, NT00–NT100). All-PSCs were constructed by integrating these resultant copolymers with a commercially available electron-accepting copolymer N2200. The resultant all-PSCs based on the ternary copolymers NT40 exhibited an impressively high power conversion efficiency over 8.0%, which was clearly superior to that obtained for devices based on the NT00 : NT100 : N2200 blended films. Further characterization of the morphology of the films revealed that the incorporation of the NT unit improved π–π stacking and a degree of phase separation, which are conducive to exciton diffusion and charge transport.